PENGARUH NIAT, MODAL SOSIAL DAN PERAN UNIVERSITAS TERHADAP MINAT BERWIRAUSAHA DI KALANGAN MAHASISWA (Studi Kasus pada Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa) - Teguh Erawati; Erly Rahma Wati (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This study aims to prove the effect of entrepreneurial intentions on interest in entrepreneurship, the influence of social capital on interest in entrepreneurship, and the influence of the role of educational institutions or universities on interest in entrepreneurship with case studies of students from Sarjanawiyata Tamansiswa University, especially the Accounting Study Program. The sample used in this study were UST Accounting students class 2017-2018 with the sampling technique using snowball sampling. The data obtained in this study is in the form of responses from respondents by filling out questionnaires that have been distributed via google form with a sample size of 83 respondents. This data is processed using IBM SPSS 22 software, with the data quality method using validity and reliability tests, while the data analysis method uses descriptive statistical tests and classical assumption tests consisting of: normality test, multicollinearity test, and heterocedasticity test, as well as for Hypothesis testing in this study uses multiple linear analysis, the coefficient of determination (R2), and the partial test (t test). Based on the data processing that has been done in this study, it shows that entrepreneurial intentions have a positive effect on interest in entrepreneurship. Social capital has a positive effect on interest in entrepreneurship. The role of universities has a negative effect on interest in entrepreneurship